Disinformation and Fake News : Old Wine in New Bottles - Kumar Ramakrishna (2018)
Disinformation, Fake News and Deliberate Online Falsehoods are nothing new. They are all forms of Propaganda. Singapore should be concerned when a Sending State’s Strategic Propaganda mechanisms and its Agents of Influence within our shores seek to achieve Information Dominance.